Clinico-epidemiology and resistance patterns of community-acquired and hospital-acquired staphylococcus aureus sepsis in children - Sahar Siddiqui; Mohd Suhail Lone; Umar Amin Qureshi; Rayees Khanday (Medical Laboratory Journal)
Background: Staphylococcus aureus (S. aureus) is a virulent bacterium responsible for a spectrum of infections, from superficial dermatological issues to severe, life-threatening sepsis. The emergence of methicillin-resistant S. aureus (MRSA) strains, encompassing both hospital-acquired (HA) and community-acquired (CA) variants, presents significant challenges to effective treatment, especially in pediatric sepsis cases. This research endeavored to characterize S. aureus sepsis in pediatric patients, differentiate between cases caused by CA S. aureus (CA-SA) and HA S. aureus (HA-SA), and evaluate patterns of antibiotic resistance. Methods: This study, conducted between January 2021 and December 2022 at the Postgraduate Department of Pediatrics, Children’s Hospital, Srinagar, Kashmir, J&K, investigated patients aged 1 month to 18 years with suspected S. aureus sepsis or disseminated disease. Standard methods (BacT Alert and Vitek II Compact) were employed for culturing various samples. Continuous data are presented as mean ± standard deviation (SD), while categorical variables are expressed as proportions. Results: Out of 56 patients, CA-SA was observed in 66.1% of cases, while HA-SA accounted for the remaining 33.9%. The cohort primarily consisted of males (62.5%) and individuals residing in rural areas (71.43%). Localized musculoskeletal symptoms were a prominent feature, present in 91.9% of patients (P ≤ 0.05). Pleuropulmonary disease showed an association with HA-SA, whereas necrotizing soft tissue infections were linked to CA-SA. Common clinical manifestations included pneumonia and abscesses. Complications (such as septic shock, respiratory failure, and multi-organ dysfunction) were more frequently encountered in patients with HA-SA. Among 50 culture-confirmed cases, 96% were identified as methicillin-resistant S. aureus (MRSA). Survival rates differed between the two groups, with 94.6% for CA-SA patients and 89.5% for HA-SA patients. Conclusion: The current study reveals a high prevalence of MRSA in pediatric sepsis, emphasizing the critical need for urgent antimicrobial stewardship. The observed distinct clinical profiles of CA-SA and HA-SA further underscore the necessity for tailored management strategies, particularly in resource-limited environments.